2022
DOI: 10.7759/cureus.22460
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasonography Beyond the Diagnosis of Pediatrics Pneumonia

Abstract: Pneumonia is a prevalent disease with considerable morbidity and mortality among the pediatric population. Early diagnosis and swift commencement of the correct treatment are vital for a favorable clinical outcome. Along with history-taking and clinical examination, imaging modalities commonly used, lung ultrasound provides a bedside, less invasive, radiation-free alternative to diagnose pneumonia when compared with other images such as chest x-ray (CXR) and computed tomography (CT) scan. It is therefore of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Radiographic failures are primarily related to the size of the pneumonic patch (<1 cm) and its posterior location. Ho et al reported that CXR showed no obvious lesions in 12 (7.4%) patients [ 10 ], and Iorio et al also reported that 4 (7.6%) had negative CXR findings [ 27 ]. Lung consolidation of less than 1 cm has been reported to be undetectable by CXR [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiographic failures are primarily related to the size of the pneumonic patch (<1 cm) and its posterior location. Ho et al reported that CXR showed no obvious lesions in 12 (7.4%) patients [ 10 ], and Iorio et al also reported that 4 (7.6%) had negative CXR findings [ 27 ]. Lung consolidation of less than 1 cm has been reported to be undetectable by CXR [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung consolidation of less than 1 cm has been reported to be undetectable by CXR [ 28 ]. They explained the failure of CXR in lesion detection due to (1) the small size and radiolucency in the early stages of the pneumonic process, (2) the posterior position of the lesion beyond the heart or mediastinum, and (3) the alveolar pattern of the pneumonic patch [ 10 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization ( 5 ) reported that pneumonia killed 740,180 children in 2019, accounting for 14% of all deaths of children under five. For the diagnosis of pediatric pneumonia, LUS has a sensitivity (95.0%) and specificity (96.1%) ( 6 ) higher than a chest x-ray and is now considered as one of the preferable first-line modality tests ( 7 ).…”
Section: Typical Applications Of Lung Ultrasound In Pediatrymentioning
confidence: 99%